Impulsive personality dimensions are associated with altered behavioral performance and neural responses in the monetary incentive delay task. (August 2017) - Gu, Ruolei; Jiang, Yang; Kiser, Seth; Black, Chelsea L.; Broster, Lucas S.; Luo, Yue-jia; Kelly, Thomas H.
Abstract: Individual differences in dimensions of impulsivity personality including disinhibition and sensation seeking modulate approach responses to reinforcing stimuli, such as drugs and money. The current study examined the effects of monetary incentive on both behavioral performance and electrophysiological activity among individuals varying in disinhibition and sensation seeking. The monetary incentive delay (MID) task was completed under electroencephalogram (EEG) recording. Behavioral data showed that higher disinhibition and sensation-seeking were associated with lower performance accuracy. Event-related potential (ERP) data showed that high reinforcement cues elicited a larger late positive component (LPC) than other conditions among high disinhibition participants, indicating its strong emotional influence. Additionally, in the neutral incentive condition, the feedback-related negativity (FRN) elicited by correct outcomes was larger than that elicited by incorrect outcomes in the high disinhibition group only. This novel finding indicates that high disinhibition participants were less likely to expect correct outcomes compared to incorrect outcomes in the neutral incentive condition. Finally, the P3 component elicited by outcome presentation showed an interaction between two impulsivity dimensions; when disinhibition level was low, the P3 was larger among high than low sensation seeking participants. Highlights: MID task accuracy decreased as a function of two dimensions of impulsivity. Impulsivity biased brain responses to reinforcing stimuli at as early as 200 ms. Under no incentive, an atypical FRN was seen in people with high disinhibition. The P3 was larger in high sensation seeking people when disinhibition was low.